Harmonization Of Healthy Living Guidelines Based On The Teachings Of The Rasulullah (Religion) And Based On Healthy Science: Harmonisasi Panduan Hidup Sehat Berdasarkan Ajaran Rasulullah (Agama) Dan Berdasarkan Ilmu Kesehatan - Jannah, Nur Laila Roudhotul (Yayasan Insan Cendekia Nusantara, 2024)
Research Background: A healthy lifestyle is one of the keys to achieving a good quality of life, not only physically, but also mentally and spiritually. This study aims to explore the relationship between the concept of a healthy lifestyle based on the teachings of the Prophet and modern health approaches, as well as see the harmony between the two in the context of everyday life. Methods: This research uses a qualitative approach with a literature review method. The main data sources consisted of Islamic religious texts, particularly hadith and the Qur'an, as well as scientific literature. Analyses were conducted to identify similarities and differences between the concepts of health in religion and modern science. Key Findings: significant alignment between the Prophet's teachings on health and modern health approaches. Both emphasise the importance of maintaining balance in diet, exercise, hygiene, and positive thinking. In addition, spiritual teachings provide additional motivation to maintain sustainable health that is often overlooked in purely scientific approaches. Contribution: The development of a more holistic concept of a healthy lifestyle, integrating spiritual aspects and modern scientific approaches. This offers a new perspective in health promotion, especially in religious communities. Conclusion: A healthy lifestyle includes not only physical, but also spiritual and mental aspects. The integration of health concepts in religion and science can increase individual awareness and compliance in maintaining health, and provide a strong basis for health promotion in the community. This study encourages the need for further empirical studies to measure the effectiveness of this approach in real life.